CULTURAL CONTENT AND INTERCULTURAL COMMUNICATIVE COMPETENCE IN INDONESIAN EFL TEXTBOOKS - Bahri, Khairil; Agustina, Noni (TELL - US JOURNAL, 2023)
Numerous investigations have delved into the cultural content and intercultural communicative competence. Nevertheless, there remains a lack of comprehensive research that directly scrutinizes these aspects within the context of Indonesian EFL textbooks, specially following new curriculum in Indonesia, the Merdeka curriculum. Therefore, this study aims to explore the representation of the culture content and intercultural communicative competence in “English for Change” and “Bahasa Inggris Tingkat Lanjut” textbooks designed for the 11th-grade students following the Merdeka Curriculum by employing content analysis. The findings suggested that both textbooks focused more on the source culture than on international and target culture. They also did not convey sufficient intercultural communicative competence. These findings imply that the government, teacher, and material developers must carefully determine and select the learning material to present a balance culture content and intercultural communicative competence in order to build students’ culture sensitivity and global awareness.